A survey on ultra wideband and ultrasonic communication for body area networks. (2016) - Basu, Sandipan; Sarkar, Mahasweta; Nagaraj, Santosh; Chinara, Suchismita
Emergence of implantable and wearable medical sensors for patient monitoring, diagnosis as well as cure has helped in the development of body area networks (BANs). For networking of these implantable and wearable devices, an appropriate choice of radio technology and communication methodology has to be made. Ultra wideband (UWB) has been identified as a solution for wireless body area networks (WBANs) in IEEE 802.15.6, but there are issues to be addressed such as attenuation inside body for implantable devices, energy efficient networking with low heat dissipation and others. Ultrasonic communication although an emerging technology promises better propagation inside body in watery media. It is known to be used without much health hazard in medical applications. This paper compares and evaluates the above two technologies for WBAN. It provides an extensive survey of existing work on UWB and ultrasonic communication for body area networks and highlights the unaddressed research challenges in using UWB and ultrasonic for WBAN applications.